Estimation of the Center Effect on Early Peritoneal Dialysis Failure: A Multilevel Modelling Approach. Issue 5 (September 2016) - Guillouët, Sonia; Veniez, Ghislaine; Verger, Christian; Béchade, Clémence; Ficheux, Maxence; Uteza, Juliette; Lobbedez, Thierry
Introduction: This study was carried out to investigate the center effect on the risk of peritoneal dialysis (PD) failure within the first 6 months of therapy using a multilevel approach. Methods: This was a retrospective cohort study based on data from the French Language Peritoneal Dialysis Registry. We analyzed 5, 406 incident patients starting PD between January 2008 and December 2012 in 128 PD centers. The end of the observation period was December 31, 2013. Results: Of the 5, 406 patients, 415 stopped PD within the first 6 months. There was a significant heterogeneity between centers (variance of the random effect: 0.10). Only 3% of the variance of the event of interest was attributable to differences between centers. At the individual level, only treatment before PD (odds ratio [OR]: 1.93 for hemodialysis and OR: 2.29 for renal transplantation) and underlying nephropathy ( p < 0.01) were associated with early PD failure. At the center level, only center experience was associated (OR: 0.78) with the risk of PD failure. Center effect accounted for 52% of the disparities between centers. Conclusion: Center effect on early PD failure is significant. Center experience is associated with a lower risk of transfer to hemodialysis.